Bevacizumab for advanced ovarian cancer treatment. A GRADE based approach - Giovanni L. Pappagallo; Valter Torri (Epidemiology, Biostatistics and Public Health)
Background: in advanced ovarian cancer, over the last 10 years no studies have demonstrated more appropriate therapeutic options compared to the current standard Carboplatin-Paclitaxel (Cb-P) regimen. Two phase III randomized studies (GOG-218 36 and ICON-7 37) have recently demonstrated the efficacy of bevacizumab (recombinant monoclonal antibody that binds with a high affinity to VEGF-A) in adjunct to Cb-P, with 12-15 months maintenance treatment. Methods: the quality of evidence provided was assessed by the use of the GRADE method. Each outcome (deemed to be essential for the purpose of evaluation of the intervention) was assessed to express the degree of confidence in the entity of the beneficial and/or harmful effects of the intervention. Thus, limitations in the quality of conducting the studies (risk of bias), direct applicability/relevance of results to the target population, and precision of results were taken into account. Results: the GOG-218 and the ICON7 study (high-risk subgroup) demonstrated with MODERATE confidence an improvement in critical outcomes PFS and OS, with an absolute reduction of 96 (GOG-218) – 103 (ICON-7) episodes of progression, and 40 (GOG-218) – 135 (ICON-7) deaths per 1 000 patients. A marked increase in risk of hypertension of Grade ≥3 was observed, with an absolute increase of 59 episodes per 1 000 patients in the ICON-7 study, and 157 episodes in the GOG-218 study, respectively, the majority of which were controlled by means of appropriate treatment. The increased risk of other adverse events considered was negligible. Conclusions: the positive effects produced should be viewed as taking prevalence over the negative effects (FAVOURABLE benefit/harm ratio).